2018
DOI: 10.1016/j.actbio.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cell-Assembled extracellular Matrix and the effect of the devitalization process

Abstract: Characterization of a Cell-Assembled extracellular Matrix (CAM) and effect of the devitalization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
4
22
0
Order By: Relevance
“…It could be seen that the expression of decorin decreased with increasing GelMa concentrations, which was similar to the case of MMP-9. Decorin is a component of the cellular matrix and is commonly found binding to type I collagen fibrils [50]. From the above observation, it was hypothesized that increasing concentrations of gelatin led to increased secretion of MMP-2, which then led to increased remodeling, seen in the form of lower levels of decorin in our results.…”
Section: Protein Expression Of Hdf-laden Scaffoldsupporting
confidence: 54%
“…It could be seen that the expression of decorin decreased with increasing GelMa concentrations, which was similar to the case of MMP-9. Decorin is a component of the cellular matrix and is commonly found binding to type I collagen fibrils [50]. From the above observation, it was hypothesized that increasing concentrations of gelatin led to increased secretion of MMP-2, which then led to increased remodeling, seen in the form of lower levels of decorin in our results.…”
Section: Protein Expression Of Hdf-laden Scaffoldsupporting
confidence: 54%
“…A zoom performed on the ECM part allowed to detect the characteristic banding pattern of collagens fibrils (Fig1D). Of note, fibril-forming collagens types I, III, and V, characterized by their ability to assemble into highly orientated supramolecular fibrils, are the main components of the human dermal extracellular matrix (Gelse 2003) and of the human dermal substitutes as assessed by proteomics (Magnan et al 2018). This result correlated with the second-harmonic generation (SHG) signal, detected by two-photon microscopy, which confirms the proper organization of these fibrillar collagens within our tissue model (Fig1E).…”
Section: Resultssupporting
confidence: 78%
“…These calibrated electric parameters were applied to a sophisticated in vitro tissue-engineered human dermal substitute, produced through the self-assembly approach in which cells produce their own extracellular matrix (Athanasiou et al 2013). Thus, the final tissue substitutes are rich in endogenous ECM proteins, as demonstrated by proteomic analyses (Magnan et al 2018), demonstrating its complex composition and similarity to the native dermis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a thorough characterization of cell-assembled ECM and the effect of the devitalization process by dehydration was performed. This study revealed the complex composition of more than 50 different proteins and no changes in the biological architecture and mechanical properties after devitalization [ 93 ]. Despite these positive results [ 94 , 95 ], the extremely long production time remained an issue for future clinical use.…”
Section: Strategies To Generate or Mimic Endothelial Basement Membranesmentioning
confidence: 99%